Gene expression profile of Scardovia spp. in the metatranscriptome of root caries - Naile DAMÉ-TEIXEIRA; Clarissa Cavalcanti Fatturi PAROLO; Marisa MALZ; Deirdre Ann DEVINE; Thuy DO (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract A few investigations of caries biofilms have identified Scardovia spp.; however, little is known about its involvement in caries pathogenesis. The purpose of this study was to assess the gene expression profile of Scardovia spp. in root caries, and compare it with other microorganisms. Clinical samples from active root caries lesions were collected. Microbial mRNA was isolated and cDNA sequenced. The function and composition of the Scardovia were investigated using two methods: a) de novo assembly of the read data and mapping to contigs, and b) reads mapping to reference genomes. Pearson correlation was performed (p < 0.05). Proportion of Scardovia inopinata and Scardovia wiggsiae sequences ranged from 0-6% in the root caries metatranscriptome. There was a positive correlation between the transcriptome of Lactobacillus spp. and Scardovia spp. (r = 0.70; p = 0.03), as well as with other Bifidobacteriaceae (r = 0.91; p = 0.0006). Genes that code for fructose 6-phosphate phosphoketolase (the key enzyme for "Bifid shunt"), as well as ABC transporters and glycosyl-hydrolases were highly expressed. In conclusion, "Bifid shunt" and starch metabolism are involved in carbohydrate metabolism of S. inopinata and S. wiggsiae in root caries. There is a positive correlation between the metabolism abundance of Lactobacillus spp., Bifidobacteriaceae members, and Scardovia in root caries.